The place of indigenous African languages in the new curriculum: An African Psychology case study - Cakata, Z. (South African Journal of Higher Education, 2023)
The role of indigenous African language in teaching and learning in South Africa is something that has been explored widely in higher education. However, these works have only resulted in the usage of these languages only to make Western knowledges intelligible to those whose first language is not English. This article argues for the need to move beyond this limited usage of indigenous languages as mere translators of Western knowledge. It calls for the usage of indigenous African languages for epistemic purposes. Using a case example of African Psychology, the article illustrates how language carries its people’s knowledges. Demonstrating that the prioritisation of colonial languages in education has cemented the myth that African people have no worthy knowledge from which to draw. This chapter illustrates the manner in which language has kept these indigenous African knowledges alive despite the epistemic violence meted against them.